Digitalization of the insurance business: Systematization of net effects through the example of Russia - Gulnara Kaigorodova; Alfiya Mustafina; Guzel Pyrkova; Mariola Grzebyk; Larisa Belinskaja (Insurance Markets and Companies, 2021)
The pace of digitalization of the insurance industry lags behind similar processes in the banking sector. The main tasks that a Russian insurer solves when using IT technologies are the automation of business operations and the formation of an online system of interaction with customers with the main focus on sales.The purpose of this study is to systematize the effects achieved by insurance market participants when introducing IT technologies and identify incentives to accelerate the insurance sector digitalization. The goal of digitalization of Russian insurers should be the formation of a client interface with a full cycle of services; the transfer to a qualitatively new level of business processes while ensuring the required level of protection; formation of fundamentally new and timely renewal of the existing insurance products. The priority areas of IT technologies used by Russian insurers are identified: cloud computing, chat bots, and information resources that provide online interaction with customers. Factors that have a stimulating effect on the digitalization of the insurance sector are identified: cost reduction, acceleration of business processes, improvement of the quality of customer service and increased competitiveness. The problems and risks of insurers that restrain the use of IT technologies are formulated: high costs of digitalization, lack of qualified personnel, cyber risks, moral and ethical problems.